1999
DOI: 10.1021/jp9839910
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study on the Keto−Enol Tautomerism of the α-Substituted Acetaldehydes XH2CCHO (X = H, BH2, CH3, NH2, OH, F, CN, NC, and Cl):  Comparison with the Tautomerism in α-Substituted Acetaldimines and Acetyl Derivatives

Abstract: Ab initio molecular orbital calculations have been performed on the R-substituted acetaldehydes XH 2 CCHdO (X)H, BH 2 , CH 3 , NH 2 , OH, F, CN, NC, and Cl) to investigate the substituent effects on the keto-enol tautomerisms. Structures for all stationary point (ketones, enols, and transition states) were optimized and characterized at the MP2(full)/6-31G* and MP2(full)/6-31G** levels of theory. Intrinsic reaction coordinates (IRC) calculations were performed in order to connect transition structures with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…[29] It has been shown that thio-enethiol tautomerization is greatly favored relative to the enolization of carbonyl compounds. The calculated relative (to the 1 t thio form) energy of the 3 t enethiol form (16.61 kcal mol -1 ) and the free energy barrier for 1 t Ǟ 3 t tautomerization (52.83 kcal mol -1 ) are not significantly different from those calculated at the MP2(full)/6-31G* level for thioacetamide [26] (17.20 kcal mol -1 and 56.66 kcal mol -1 ). The values of the free energies of the 1 t Ǟ 4 t and 1 o Ǟ 4 o tautomerizations are comparable, whereas in the assisted mechanisms the free energy barriers for 4-methyl-1,3-dihydro-2H-1,5-benzodiazepine-2-thione tautomerizations are smaller than those for 4-methyl-1,3-dihydro-2H-1,5-benzodiazepin-2-one.…”
Section: Tautomerism Of 4-methyl-13-dihydro-2h-15-benzodiazepine-2-mentioning
confidence: 68%
See 1 more Smart Citation
“…[29] It has been shown that thio-enethiol tautomerization is greatly favored relative to the enolization of carbonyl compounds. The calculated relative (to the 1 t thio form) energy of the 3 t enethiol form (16.61 kcal mol -1 ) and the free energy barrier for 1 t Ǟ 3 t tautomerization (52.83 kcal mol -1 ) are not significantly different from those calculated at the MP2(full)/6-31G* level for thioacetamide [26] (17.20 kcal mol -1 and 56.66 kcal mol -1 ). The values of the free energies of the 1 t Ǟ 4 t and 1 o Ǟ 4 o tautomerizations are comparable, whereas in the assisted mechanisms the free energy barriers for 4-methyl-1,3-dihydro-2H-1,5-benzodiazepine-2-thione tautomerizations are smaller than those for 4-methyl-1,3-dihydro-2H-1,5-benzodiazepin-2-one.…”
Section: Tautomerism Of 4-methyl-13-dihydro-2h-15-benzodiazepine-2-mentioning
confidence: 68%
“…The high value of free energy for the 1 o Ǟ 4 o tautomerization is consistent with those for imineenamine tautomerization in α-substituted acetaldimines. [26] The effect of a dielectric solvent on the free energies of TS(1 o Ǟ4 o ) and TS(1 o Ǟ3 o ) transition states is negligible (changes are smaller than 1 kcal mol -1 ). However, the free energy barrier for 1 o Ǟ 2 o transformation in solution is higher than in the gas phase, by 5.11 kcal mol -1 .…”
Section: Intramolecular Proton Transfermentioning
confidence: 99%
“…The bond lengthening was accompanied with a decrease in the electron density (Tables 2A and 2B). The BH 2 substituent has no lone pairs but the B atom has an empty π orbital [13] which can accept the electron density from C=C in imine and C=N in enamine.…”
Section: Effect Of Substituentsmentioning
confidence: 99%
“…Enolizations have, of course, been studied extensively, both theoreticallyand experimentally, ever since Lapworth's classic paper on acetone enolization over a century ago. It was R. P. Bell who originally proved that ketone enolization can be catalyzed jointly by a general base and general acid .…”
Section: Introductionmentioning
confidence: 99%